Prognostic value of cardiac power output to left ventricular mass in patients with left ventricular dysfunction and dobutamine stress echo negative by wall motion criteria. (29th April 2016) - Cortigiani, Lauro; Sorbo, Simone; Miccoli, Mario; Scali, Maria Chiara; Simioniuc, Anca; Morrone, Doralisa; Bovenzi, Francesco; Marzilli, Mario; Dini, Frank Lloyd
Abstract : Aims: Cardiac power output to left ventricular mass (power/mass) is an index of myocardial efficiency reflecting the rate at which cardiac work is delivered with respect to the potential energy stored in the left ventricular mass. In the present study, we sought to investigate the capability of power/mass assessed at peak of dobutamine stress echocardiography to predict mortality in patients with ischaemic cardiomyopathy and no inducible ischaemia. Methods and results: One-hundred eleven patients (95 males; age 68 ± 10 years) with 35 ± 7% mean left ventricular ejection fraction and a dobutamine stress echocardiography (up to 40 µg/kg/min) negative by wall motion criteria formed the study population. Power/mass at peak stress was obtained as the product of a constant ( K = 2.22 × 10 −1 ) with cardiac output and the mean arterial pressure divided by left ventricular mass to convert the units to W/100 g. Patients were followed up for a median of 29 months (inter-quartile range 16–72 months). All-cause mortality was the only accepted clinical end point. Mean peak-stress power/mass was 0.70 ± 0.31 W/100 g. During follow-up, 29 deaths (26%) were registered. With a receiver operating characteristic analysis, a peak-stress power/mass ≤0.50 W/100 g [area under curve 0.72 (95% CI 0.63; 0.80), sensitivity 59%, specificity 80%] was the best value for predicting mortality. Univariate prognostic indicators were age, male sex, peak-stress ejection fraction, peak-stress stroke volume, peak-stress cardiac output, peak-stress cardiac power output ≤1.48 W, and peak-stress power/mass ≤0.50 W/100 g. At multivariate analysis, age (HR 1.08, 95% CI 1.04; 1.14; P = 0.004) and peak-stress power/mass ≤0.50 W/100 g (HR 4.05, 95% CI 1.36; 12.00; P = 0.01) provided independent prognostic information. Three-year mortality was 14% in patients with peak-stress power/mass >0.50 W/100 g and 47% in those with peak-stress power/mass ≤0.50 W/100 g (log-rank 20.4; P < 0.0001). Conclusion: Power/mass assessed at peak of dobutamine stress echocardiography allows effective prognostication in patients with ischaemic cardiomyopathy and test result negative by wall motion criteria. In particular, a peak-stress power/mass ≤50 W/100 g is a strong and multivariable predictor of mortality.